(untitled) (Gestão & Regionalidade, 2025)
Research was carried out to identify and analyze the differences between the tariffs for services related to current accounts of natural person charged by the four largest publicly traded Brazilian banks in 2019. Documentary, descriptive / exploratory research identified that the positive evolution of banks’ profits in Brazil is notorious, even in recessionary or low growth economic conditions. The balance sheets analyzed show that revenue from fees for providing services play an important role in this result. It was also identified that the tariffs are of great importance in the spending structure of Brazilian families but have little visibility and are difficult to compare by service users. Additionally, the comparative analysis of the various tariff packages and specific tariffs led to the conclusion that the differences between banks are relatively small, considering the large scope of services and the fact that the sector must be characterized by competitive practices